2012
DOI: 10.1194/jlr.p029785
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic low density lipoprotein phenotype in long-term survivors of childhood acute lymphoblastic leukemia

Abstract: Supplementary key words cancer • dyslipidemias • lipids • lipoproteins • LDL subfractionsAcute lymphoblastic leukemia (ALL) constitutes more than 80% of newly diagnosed acute leukemias in children and has a current fi ve-year overall survival rate exceeding 85 percent ( 1 ). At the same time, data from the Childhood Cancer Survivor Study (CCSS) suggest that adult survivors of childhood leukemia are at signifi cantly increased risk for myocardial infarction [Hazard rate (HR) 3.3; 95% CI, range 1.2-8.6 ] and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…18,31 In our study, elevated blood pressure was significantly associated with male sex, which is also a known risk factor in the general population, especially among young and middle-aged adults. 32 This risk factor has already been described in adult survivors of childhood AL.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…18,31 In our study, elevated blood pressure was significantly associated with male sex, which is also a known risk factor in the general population, especially among young and middle-aged adults. 32 This risk factor has already been described in adult survivors of childhood AL.…”
mentioning
confidence: 76%
“…Investigators in the USA have recently shown that CNS irradiation affects lipid profiles and in particular HDL cholesterol levels. 31 However, the long-term effect of CNS irradiation on blood pressure among adult survivors of childhood AL remains poorly understood. In several studies concerning acute lymphoblastic leukemia survivors, no significant difference in blood pressure between irradiated and non-irradiated patients has been described.…”
Section: Number Of Cases (%) 95% CImentioning
confidence: 99%
“…The lipoprotein metabolism is previously shown to be affected by gender, age and BMI [27][28][29]. In the present study we performed gender-, age-and BMI-based analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Gender, age and BMI are previously shown to affect lipoprotein metabolism in healthy subjects [27][28][29]. Here, the study population was categorized into gender, BMI or age groups and plasma lipid concentrations in each patient group were compared to the respective control group.…”
Section: Lipid Profile Of Acute Leukemia Patients Versus Healthy Subjmentioning
confidence: 99%
“…Survivors of childhood acute lymphoblastic leukemia (ALL) tend to have greater risk of obesity3711), glucose intolerance12), lipid abnormalities913), and cardiovascular events14) compared to equivalently aged members of the general population. Table 1 summarizes the possible mechanisms underlying metabolic syndrome development that induced by different cancer treatments.…”
Section: Characteristics Of Metabolic Syndrome In Cancer Survivorsmentioning
confidence: 99%